Capacity Building for Health Cadres in Preventing Degenerative Diseases - Effendi; Budhi Setianto; Yauwan Tobing Lukiyono; Diffran Nobel Bistara; Nikmatus Sa'adah (Universitas Nahdlatul Ulama Surabaya, 2024)
Degenerative diseases are conditions that cause deterioration of cell and organ function, with high mortality rates. These diseases are closely related to modern lifestyles, including decreased diet and physical activity. The purpose of this activity is to provide counselling and education to the community of RW 07 Wonokromo Village regarding the prevention of degenerative diseases and increase the knowledge and awareness of the community regarding this matter. The activity was carried out by giving a pre-test to participants to measure their initial understanding of degenerative diseases. Furthermore, education was carried out using the lecture method using media such as laptops and LCD screens to facilitate visualisation of the material. After the delivery of the material, a question and answer session was held as a post-test to measure the increase in participants' knowledge. The programme was attended by 90 participants with various age ranges. The pre-test results showed that the participants still had minimal knowledge about degenerative diseases. After education, the post-test results showed a significant increase in knowledge (p < 0.05). The mean value of the pre-test was 68, while the post-test increased to 889, showing a significant increase. Education on degenerative diseases was effective in improving participants' knowledge. This activity is expected to be passed on by participants to the surrounding community to prevent degenerative diseases and maintain health. Obstacles faced such as inadequate venues can be overcome with better preparation in the future. Suggestions or Recommendations: It is recommended that education and counselling activities on degenerative diseases be carried out regularly, involving more people, and accompanied by more adequate facilities. In addition, further training for health cadres would help them become effective agents of education in the community.